LA INSTITUCIÓN JURÍDICA DEL ABANDONO EN PROCEDIMIENTOS VOLUNTARIOS SEÑALADO EN EL ART. 334 DEL CÓDIGO ORGÁNICO GENERAL DE PROCESOS AFECTA LA SEGURIDAD JURÍDICA DE LOS ACCIONANTES POR CUANTO NO EXISTE LEGÍTIMO CONTRADICTOR - Sosa Guamán, Brian Alexander (2019)
The present work of juridical investigation denominated "THE LEGAL INSTITUTION OF THE ABANDONMENT IN VOLUNTARY PROCEDURES INDICATED IN THE ART. 334 OF THE GENERAL ORGANIC PROCESS CODE AFFECTS THE LEGAL SECURITY OF THE ACCIDENTS WHERE THERE IS NO LEGITIMATE CONTRADICTOR ", implicitly involves a legal, doctrinal, conceptual and social problem, in terms of the lack of regulations on the procedural application in voluntary processes, that support the rights and guarantees enshrined in our Constitution, as a consequence of that lack of regulations are affected rights of citizenship in general, therefore people are distressed by not being able to access a prompt and timely justice that makes prevail their rights. In the research, the general objective sought was "to carry out a conceptual, doctrinal, legal and social study of the legal institution of abandonment and its constitutional effects in voluntary procedures established by the General Organic Code of Processes". As long as there is a lack of regulations in terms of making the rights of those who have proposed actions in voluntary procedures prevail, justice administrators leave the defendants of these causes in complete defenselessness, without applying constitutional rights. Repetitive manner determined violation when it has been incurred with a decision to abandon the procedure. 5 Consequently, in my last specific objective, I consider: "submit a proposal for reform to the General Organic Code of Processes, which the institution of abandonment does not affect the legal security of people who have proposed an action in voluntary procedure", receiving all the information of legal professionals, as well as a broad conceptual study, legal doctrine and comparative legislation proceeds to establish the greatest viability to leave in the right rights that are evidently violated, thus benefiting the judicial system and society in general.